0136 Evaluation of MRI-Based Soft-Tissue and Craniofacial Phenotypes in Diversity Outbred Mice and Founder Strains. (27th April 2018) - Nguyen, T T; Keenan, B T; Galante, R; Wiemken, A S; Lin, T C; Azad, N; Brake, L A; Schwab, R J; Pack, A I
Abstract: Introduction: Increased volume of upper airway soft-tissues, tongue fat deposition, and restricted craniofacial dimensions are anatomic risk factors for Obstructive Sleep Apnea (OSA). A new strategy for identifying associated genes is to leverage outbred mouse models and examine associations with intermediate phenotypes. We quantified phenotypes in Diversity Outbred (DO) mice and the 8 inbred and wild-derived Founder strains. We hypothesized that these phenotypes would significantly differ among Founders, suggesting associations with underlying genetic architecture. Methods: Magnetic Resonance Imaging (MRI)-base phenotypes were quantified within 6–7 month-old male DO mice (n=47) and male mice from the 5 inbred [A/J (n=3), C57BL/6J (n=3), 129S1/SvlmJ (n=3), NOD/LtJ (n=3), NZO/HILtJ (n=3)] and 3 wild-derived [CAST/EiJ (n=2), PWK/PhJ (n=3), WSB/EiJ (n=3)] Founder strains. All mice were group housed and fed the same diet. MRI was performed to quantify tongue volume, tongue fat volume, tongue fat percentage, mandibular divergence and length, and the intramandibular volume (IMV) using Amira 5.4.1 software. Phenotypes were compared among Founders and the variability within DO mice was evaluated. Results: There were significant differences among the Founder strains for tongue volume (p<0.0001), tongue fat volume (p=0.0002), and tongue fat percentage (p=0.0007), as well as mandibular width at the gonion (p=0.0011) and 2 nd molar (p=0.0047) and the IMV (p=0.0010). No differences among Founders were seen for other mandibular measures (divergence [p=0.4211], length [p=0.0896], or width at 1 st molar [p=0.5040], and condyle [p=0.5961]). There was high variability for MRI-based phenotypes in the DO mice; values spanned or extended beyond the ranges observed across Founders, reflecting increased genetic diversity. Conclusion: We quantified tongue size and craniofacial dimensions using MRI-based imaging in DO and Founder mice. Differences in tongue size, tongue fat and fat percentage, mandibular width and IMV among Founders suggest genetic associations with these phenotypes. High variability in DO mice indicates these phenotypes are suitable for genetic association studies in outbred mice populations. Genetic analyses in these mice may identify specific genes related to craniofacial size or tongue fat involved in OSA pathogenesis. Support (If Any): Funded by NIH P01 HL094307.